1993
DOI: 10.1029/93jd02293
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of triggered‐lightning flashes in Florida and Alabama

Abstract: Channel base currents from triggered lightning were measured at the NASA Kennedy Space Center, Florida, during summer 1990 and at Fort McClellan, Alabama, during summer 1991. Additionally, 16‐mm cinematic records with 3‐ or 5‐ms resolution were obtained for all flashes, and streak camera records were obtained for three of the Florida flashes. The 17 flashes analyzed here contained 69 strokes, all lowering negative charge from cloud to ground. Statistics on interstroke interval, no‐current interstroke interval,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
173
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 199 publications
(190 citation statements)
references
References 25 publications
17
173
0
Order By: Relevance
“…At the ICLRT, lightning is triggered (artificially initiated) from natural overhead thunderclouds using the rocket-and-wire technique [e.g., Newman, 1958;Fieux et al, 1975;Uman et al, 1997;Rakov, 1999;Rakov and Uman, 2003]. Triggered lightning is typically composed of an initial stage involving an upward-propagating positive leader initiating a relatively steady current of the order of 100 A with a duration of hundreds of milliseconds, followed by one or more dart leader-return stroke sequences which are very similar to the strokes following the first stroke in natural downward lightning [e.g., Fisher et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…At the ICLRT, lightning is triggered (artificially initiated) from natural overhead thunderclouds using the rocket-and-wire technique [e.g., Newman, 1958;Fieux et al, 1975;Uman et al, 1997;Rakov, 1999;Rakov and Uman, 2003]. Triggered lightning is typically composed of an initial stage involving an upward-propagating positive leader initiating a relatively steady current of the order of 100 A with a duration of hundreds of milliseconds, followed by one or more dart leader-return stroke sequences which are very similar to the strokes following the first stroke in natural downward lightning [e.g., Fisher et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming I ഛ 10 kA, the effective acceleration associated with the magnetic pinching forces is which is significantly less than the air backflow acceleration a 0 Х 7.07ϫ 10 4 m/s 2 . Therefore, during most of the continuing current stage, with a typical current I c = 1000-100 A, 5 the pinch instability is much weaker then the RayleighTaylor instability. In the following calculations, the continuing current is assumed constant, with a value I c = 1000 A.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In a recent book, Rakov and Uman 6 pointed out that bead lightning clearly involves an already existing lightning channel, but there is no consensus view of the physical mechanism for its formation. This periodic structure has been recently recorded using a fast charge-coupled-device ͑CCD͒ camera during a series of triggered lightning experiments carried out in the International Center for Triggered and Natural Lightning in Cachoeira Paulista, SP, Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often observed that there are humps embedded in the continuing currents, termed M components. These almost symmetric swells have rise times of about few hundred microseconds and amplitude ranging from few hundreds to about thousand Amperes [3,[5][6][7][8][9][10].…”
Section: Lempsmentioning
confidence: 99%